UPAYA MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERTIF TIPE STAD PADA MURID KELAS V. MIS MUHAMMADIYAH BUJUNG TANGAYA V - Nur Rahmi; Rahmawati Hidayah (ASIAN PUBLISHER, 2022)
The goal to be achieved through this research is to improve the learning outcomes of Indonesian language students of grade V mis muhammadiyah bujung tangaya V by using the STAD Type cooperative learning model. This type of research is Classroom Action Research. The implementation of this P2K was carried out at mis muhammadiyah bujung tangaya V, in the odd semester of the 2022/2023 school year for 2 months, starting from August to October 2022. The research subjects were class V students of mis muhammadiyah bujung tangaya V, who were enrolled in lesson 2022/2023 as many as 20 students consisting of 7 boys and 13 girls. Based on the results of the study it can be concluded that the role of cooperative learning with the STAD type can increase the activity of the teaching and learning process. From the observation results show that there is an increase from cycle I and cycle II. Ability in group discussions also experienced significant progress. This is because students are getting used to group learning. Student mastery of learning material shows an increase. This can be shown the results of the average daily repetition.